Competence for basic midwifery practice: Updating the ICM essential competencies. (November 2018) - Butler, Michelle M.; Fullerton, Judith T.; Aman, Cheryl
Highlights: This study involved a representative sample of midwifery experts worldwide. An initial set of 791 competencies and components was reduced to 320. Most core midwifery competencies were endorsed, except those related to abortion. Professional and personal competencies were strongly endorsed. Few competencies relating to the wider midwifery role were endorsed. Abstract: Objective: To obtain consensus amongst midwifery experts globally about the essential competencies for basic midwifery practice. Design: A modified Delphi approach, involving a three-round online survey. Participants: Midwifery leaders, educators and regulators in all ICM regions, along with representatives of organisations affiliated to ICM. Methods: The research team worked closely with a Core Working Group and a Task Force. An initial set of competencies and components was developed through a content analysis of existing competency documents and presented to participants in Round 1 of the survey. Items identified as essential by at least 85% of participants were endorsed. Remaining items and new items identified by participants were returned to participants in Rounds 2 and 3 for further rating. Findings: The study achieved a wide sample representative of midwifery experts across all ICM regions and countries, language groups, and income categories. Only a small number of competencies relating to the wider role of the midwife were endorsed as essential competencies. Competencies and components relating to professional and personal attributes were extended. Although most competencies and components relating to core midwifery practice were endorsed as essential competencies, several were rejected relating to abortion-related care, cancer screening, infertility, and gynaecology. Findings are, nevertheless, highly consistent with the scope of practice delineated in the current 2010/2013 version of the ICM Essential Competencies for Basic Midwifery Practice. Key conclusions and implications for practice: The extension of professional and personal attributes reflects the recent emphasis on respectful midwifery care. The rejection of most of the additional competencies and components relating to the wider role of the midwife and endorsement of most of those considered to relate to core midwifery practice indicates that the scope of midwifery practice remains essentially unchanged through 2017.